Early Childhood Sexual Abuse and the Criminal Justice System: Challenges, Legal Reform, and Victim Rehabilitation in Indonesia - Hamamah, Fatin; Hermanto, Hermanto; Darwanto, Darwanto; Rohadin, Rohadin; Aos, Aos (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2025)
Early childhood sexual abuse is a severe and traumatic crime with long-term physical and psychological impacts. This study offers an original contribution by critically analysing the effectiveness of Indonesia’s criminal justice system in addressing such cases, particularly from the perspective of victim protection and rehabilitation. The main objective is to assess how well criminal law in Indonesia provides justice for victims and to identify the barriers that hinder effective legal implementation. Employing a qualitative approach with a case study method, data were collected through in-depth interviews with legal practitioners and child protection activists, as well as through document analysis and selected case reviews. The findings reveal that while Indonesia's legal framework theoretically supports child protection, significant gaps persist between legal norms and their enforcement. These include poor inter-agency coordination, low sensitivity to victims' needs, limited access to rehabilitation services, and the persistence of social stigma. The practical implications of this research suggest the need for targeted legal reforms, including enhanced training for law enforcement officers, improved victim-centered procedures, and the strengthening of rehabilitation support. These measures are essential to ensure a more just and effective response to early childhood sexual abuse.